Optimal spaces for those living with dementia: principles and evidence - Barrett, Peter; Sharma, Monika; Zeisel, John (Building research and information : the international journal of research, development and demonstration, 2019)
This paper presents a synthesis of diverse and disparate evidence in the research literature that provide insights into the impacts of aspects of the built environment on the wellbeing of those living with dementia. The individually focused findings are structured into a set of practical design parameters driven by three overarching needs-driven design principles: manageable cognitive load, clear sequencing and appropriate level of stimulation. These needs are contextualized within a general model that suggests that action in any one area (such as the built environment) also has to take into account other key dimensions, namely any support from the caring/social environment and any pharmacological treatment. Addressing these elements holistically should maximize the opportunity to improve the quality of life of the individual. This paper, however, explicitly focuses on the built environment.